ANAK-ANAK DAN TAMBANG (MENGUAK TABIR KETERLIBATAN ANAK-ANAK DALAM AKTIVITAS PENAMBANGAN TIMAH DI DESA PENYAK KABUPATEN BANGKA TENGAH) - Musliyandi, Rini Archda Saputri, Rendy, (JIANA ( Jurnal Ilmu Administrasi Negara ), 2020)
The involvement of children in mining activities in Bangka has become commonplace. Whereas the involvement of children in mining activities has a direct and indirect impact on the life of the child, now and in the future. Some of the impacts that can be caused: safety threats, illness, until dropping out of school. This study aims to look at social conditions in Penyak Village, Central Bangka Regency related to the involvement of children in mining activities. The research method was carried out by conducting in-depth interviews (in-depth interviews) to the families of tin miners in Penyak Village, Central Bangka Regency, especially those involving children in mining activities. The results showed that the involvement of children in mining activities in Penyak Village had been going on for generations from generation to generation. Economic factors are not the main motive of involving children in mining activities. The lack of educational facilities, the lack of parental awareness of the importance of education, and the pragmatic attitude of the community towards life are factors that cause this phenomenon. Therefore, educational assistance is needed for tin mining families in Penyak Village in particular, and the Bangka community in general on the importance of deciding the involvement of children in mining activities so that children can focus on preparing their future well. Besides, there is a need for a policy that can condition the community to reduce the amount of involvement of children in tin mining activities on the island of Bangka.